Strategi Kreatif Konten Kreator Podcast Musuh Masyarakat Berjudul: "Kami Mendukung Childfree (Bersama Gita Savitri)" - Eliezer, Kefas Yezkiel Amadio; Kusumawati, Dyah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
Creative strategies of content need to be implemented to attract the audience. Musuh Masyarakat is an Podcast owned by Noice, released since 2019 with total of 139 episodes for 5 seasons. Podcast Musuh Masyarakat presents controversial content about current issue in society. This study aims to determine the Creative Strategy of Podcast Musuh Masyarakat’s Content Creator Titled: “Kami Mendukung Childfree (Bersama Gita Savitri)”. The method of this research is case study with in in-depth interviews, observation, and documentation as data collection techniques. Researchers use Peter Pringle program planning model. The results of the study shows several creative strategies used in Podcast Musuh Masyarakat. Noice determines the podcaster first before planning the program. The concept of program based on the big name Podcaster. In presenting Podcasts, Podcasters don’t use scripts so Podcasters can freely present topics. Childfree topic was brought up because childfree is becoming current issue because of Gita Savitri.